The Sociological Perspective on the Impact of Family Divorce on Children - Nasution, Muhamad Guntur Muntaha; Meli Fauziah (Social Impact Journal, 2024)
This paper aims to analyze the leadership role of Governor Ridwan Kamil in the West Java Government Era in implementing the Digital Village Program. Family divorce is a social phenomenon that is increasingly common in contemporary society. In this context, the impact on children is of primary concern, as it has far-reaching implications for their development and well-being. This research aims to reveal a sociological perspective on family divorce and its impact on children. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews with divorced parents, children from divorced families, and community members around Mangkalaya Village. The data collected was analyzed thematically to identify patterns and themes that emerged. In this article, conflict theory is used, conflict can help integration or can cause conflict according to Ralp Dahrendorf to analyze cases of divorce in families and their impact on children. The research results show that family divorce affects children multidimensionally, including emotions, behavior and psychological well-being. Children from divorced families tend to experience stress, identity confusion, and difficulties in building healthy social relationships. The conclusion of this research is the importance of a holistic approach in overcoming the social impacts of family divorce, by paying attention to community support, psychological interventions, and the role of the family. more broadly in supporting the well-being of children in divorce situations.